Принципи стимулювання праці суддів в сучасних умовах - Подорожній, Є. Ю.; Podorozhnii, Ye. Yu.; Вінніков, С. В.; Vinnikov, S. V.; Подорожній Євген Юрійович (Наше право. - 2024. - № 1. - С. 302-307, 2024)
Встановлено коло та розкрито зміст принципів стимулювання праці судді в сучасних умовах. Узагальнено, що принципам стимулювання праці суддів, як правовій категорії, притаманні характерні особливості, зокрема: 1) принципи визначають основи нормативно-правового регулювання стимулювання праці суддів; 2) здійснюють важливий вплив на нормотворчу та правозастосовну діяльність; 3) забезпечують сингулярність правового регулювання стимулювання праці суддів; 4) принципи виступають важливим критерієм для створення системи дієвих та ефективних стимулів для забезпечення ефективної діяльності суддів.

It has been established that the principles of incentivizing judges are most appropriately understood as certain ideas, basic provisions shaping the principles of regulatory framework in this area, and creating an effective mechanism for legal incentives to influence judges’ work. A classification of principles of incentivizing judges has been conducted, divided into: 1) general legal principles (principle of rule of law; principle of legality; principle of transparency; principles of fairness and equality); 2) special principles, which include: a) motivation principle, involving the process of encouraging judges to pursue beneficial goals and efficiency in their professional activities; b) timeliness principle, stimulating judges’ work directly after the action, as a large interval between the desired result and the incentive diminishes the motivating nature of the stimulus; c) openness and transparency principle, obliging responsible individuals for incentivizing judges’ work to ensure accessibility to information regarding types of incentives for conscientious work of judges; d) combination of material and non-material incentives (comprehensiveness); e) profitability principle, ensuring that the physical and psychological efforts in performing the work correspond to the strength of the incentive for completing the work; f) reward guarantee principle. It is summarized that the principles of incentivizing judges, as a legal category, have characteristic features, including: 1) determining the bases of normative-legal regulation of incentivizing judges’ work; 2) exerting significant influence on legislative and judicial activities; 3) ensuring the uniqueness of legal regulation of incentivizing judges’ work; 4) serving as an important criterion for creating a system of effective incentives to ensure efficient judicial activities.

Установлен круг и раскрыто содержание принципов стимулирования труда судьи в современных условиях. Обобщено, что принципам стимулирования труда судей, как правовой категории, характерны особенности, в частности: 1) принципы определяют основы нормативно-правового регулирования стимулирования труда судей; 2) оказывают важное влияние на нормотворческую и правоприменительную деятельность; 3) обеспечивают сингулярность правового регулирования стимулирования труда судей; 4) принципы являются важным критерием для создания системы действенных и эффективных стимулов для обеспечения эффективной деятельности судей.
Keywords: принципи; принципи права; стимулювання праці; заохочення; судді; principles; legal principles; labor stimulation; encouragement; judges; принципы; принципы права; стимулирование труда; поощрение; судьи